Cognitive Science: Contributions to Educational Practice - Languis, Marlin (Routledge Library Editions: Education, 1991)
This volume brings together theory, research and development in cognitive neuro-science. It investigates the neural processes involved in cognition and learning, using developments in computer technology to study the brain in action and other topographic brain mapping. Electrical activity patterns of the brain in the learning processes are displayed through these techniques. Part 1 delineates neuroscience application to educational perspectives. Part 2 reports on emotional and learning disorders, such as autism, while Part 3 applies cognitive science to educational and mental health, as well as to settings such as the classroom, rehabilitation centre or doctor's office.